Leadership in PhD (LeaP): A longitudinal leadership skill building program for underrepresented biomedical research trainees - Doles, Mali D.; Kang, Ji Yun; Scholl, Linda M.; Doles, Jason D. (Frontiers in Education, 2023)
Increasing diversity in the biomedical research workforce is a critical national issue. Particularly concerning is the lack of representation at more advanced career stages/in leadership positions. While there are numerous institutional initiatives promoting professional research skills (i.e. grant writing, presenting, networking) for underrepresented (UR) PhD trainees, there are comparatively fewer opportunities for leadership development. We present a blueprint for Leadership in PhD (LeaP), a cohort-based program aiming to equip UR biomedical research trainees with skills to succeed as academic, industry, and community leaders. In contrast to intensive short-term programs or workshops, LeaP is a longitudinal 4-year experience with an emphasis on self-directed and experiential learning. First year trainees receive foundational didactic instruction on core leadership concepts coupled with facilitated peer discussions and one-on-one coaching support. We outline a program evaluation framework that assesses student learning, satisfaction, and program efficacy. Evaluation data from the inaugural year is presented and discussed.